2015
DOI: 10.1038/ijo.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal outcomes for pregnancies before and after gastric bypass surgery

Abstract: BACKGROUND Interaction between maternal obesity, intrauterine environment and adverse clinical outcomes of newborns has been described. METHODS Using statewide birth certificate data, this retrospective, matched-control cohort study compared paired birth weights and complications of infants born to women before and after Roux-en-Y gastric bypass surgery (RYGB) and to matched obese non-operated women in several different groups. Women who had given birth to a child before and after RYGB (group 1; n = 295 matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 54 publications
1
71
1
2
Order By: Relevance
“…The 6 studies included in this section found either no difference or an increased risk of SGA neonates among bariatric surgery patients [13,15,[19][20][21]23] while our data suggests an increased risk of SGA among the bariatric surgery woman as compared to the controls. However, this is potentially due to the same reasons as listed above for IUGR.…”
Section: Sgacontrasting
confidence: 49%
See 1 more Smart Citation
“…The 6 studies included in this section found either no difference or an increased risk of SGA neonates among bariatric surgery patients [13,15,[19][20][21]23] while our data suggests an increased risk of SGA among the bariatric surgery woman as compared to the controls. However, this is potentially due to the same reasons as listed above for IUGR.…”
Section: Sgacontrasting
confidence: 49%
“…While there were a few select papers that showed no difference, the majority of the studies reviewed showed a significant decrease in the rates of both LGA and macrosomic neonates in the bariatric surgery patient. Women who gain less weight during the pregnancy, on average, have a decreased chance of delivering a LGA or macrosomic neonate [15] . Our analysis found there was a decreased incidence of both LGA and macrosomia in the bariatric surgical women who are obese, as compared to the obese controls.…”
Section: Sgamentioning
confidence: 99%
“…Previous retrospective reports and register studies have addressed pregnancy complications and pregnancy outcomes following gastric bypass and have demonstrated beneficial effects such as reduced incidence of pre-existing and gestational diabetes mellitus (GDM) [8,9], possibly contributing to a lower prevalence of large for gestational age (LGA) offspring [10][11][12]. However, a marked increase in the prevalence of small for gestational age (SGA) neonates, along with a small increase in the rates of stillbirths or neonatal deaths, indicates a higher risk for perinatal morbidity and mortality [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, weight gain during pregnancy was found to positively correlate with the newborn’s body weight 54. This influence of maternal weight on neonatal weight is important at birth time, but also, and probably most importantly, there is a great amount of scientific evidence supporting that it significantly influences intrauterine fetal development, portending an increased risk of overweight and obesity during adolescence and adulthood 5557…”
Section: Introductionmentioning
confidence: 99%
“…They found that babies born after maternal BS had lower birth weight, lower gestational age, 3.3-times lower risk of LGA, and 2.3-times higher risk of SGA than infants born to matched women without BS. In addition, a recent retrospective, matched-control cohort study has compared birth weights of babies born to women with pregnancies before and after RYGB surgery 54. Interestingly, the authors communicated that women who had undergone RYGB had a significantly lower risk for having an LGA newborn, but also a significantly increased risk for delivering an SGA neonate, than nonoperated women closely matched by age and BMI before pregnancy 54…”
Section: Introductionmentioning
confidence: 99%